Minerva Louise on Christmas Eve - Stoeke, Janet Morgan (Dutton Children's Books, 2007)
Minerva Louise follows a farmer in a red hat from a snowy rooftop, down a "well," and into the house with the red curtains, where she finds a tree decorated with sparkling eggs.